Computing Volume of the Heart’s Right Ventricle Using 2D Echocardiography Images - Ušinskas, Andrius; Meilūnas, Mečislavas; Paulinas, Mantas; Miniotas, Darius; Zakarkaitė, Diana; Matačiūnas, Mindaugas; Ušinskienė, Jurgita; Laucevičius, Aleksandras (Mathematical Modelling and Analysis, 2014)
This paper presents a new way for computing the volume of the heart’s right ventricle. The technique involves manual marking of three critical contours of the ventricle’s regions on 2D echocardiography images. The contours are then deformed semi-automatically to keep them orthogonal and concurrent in four-chamber plane, transverse (short-axis) plane, and lateral plane. The ventricle’s surface is generated and its volume computed automatically. The proposed model was validated by comparing its estimate with actual measurements using 3D echocardiography imaging.